2021
DOI: 10.1108/ijbpa-10-2020-0088
|View full text |Cite
|
Sign up to set email alerts
|

Technology-based multi-tiered building diagnosis framework

Abstract: PurposeA building deteriorates over time due to aging, wear and tear, and inadequate maintenance. Building diagnosis requires a sound knowledge of engineering, building defects, and detection tools to assess the condition of a building. The physical deterioration of a building reduces its ability to perform its intended function, while environmental deterioration influences the comfort and health of building occupants. This study presents a multi-tiered framework for the inspection of building elements and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 66 publications
(70 reference statements)
0
3
0
Order By: Relevance
“…The study did not include the acoustics quality in their field measurements but rather in the questionnaire when students were surveyed. Faqih et al (2021) employed a case study to analyze a framework with different levels. It was observed that the framework provided a time-saving opportunity for the analysis of a building's physical and environmental condition.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study did not include the acoustics quality in their field measurements but rather in the questionnaire when students were surveyed. Faqih et al (2021) employed a case study to analyze a framework with different levels. It was observed that the framework provided a time-saving opportunity for the analysis of a building's physical and environmental condition.…”
Section: Introductionmentioning
confidence: 99%
“…This would consequently reduce repair cost and hinder further deterioration of the buildings. Faqih et al (2021) developed a model that assesses the physical and environmental conditions of a building on a building information modeling (BIM) framework. The model takes into account the elements that impact the physico-environmental condition of a building.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation